Exploring Studies on the Effect of Indirect Instruction on Student’s Achievement in Chemistry using Meta-Analytical Approach - Ngozi , M. Eya; Florence , O. Attah; Ijeoma , H.N. Nwoji (International Journal of Psychosocial Rehabilitation, 2024)
The trend of inconclusiveness in the studies on effect of indirect instructional methods/strategies on students’ achievement in chemistry necessitated this study. The purpose of the study was to integrate the results of the previous research studies on the effect of indirect instructional methods on students’ academic achievement in chemistry in Nigeria through a meta-analytic approach. Three research questions were posed and two hypotheses formulated to guide the study. The population of the study consisted of all previous research reports on indirect instructional methods and students’ academic achievement in Nigeria between 1990 and 2017. The sample consisted of published and unpublished Ph.D and master’s research reports on the effect of indirect instructional methods on students’ academic achievement in chemistry between 1990-2017.Ttwenty nine (29) Studies constituted the sample. The data collected were analysed using percentages statistical transformations and computation of Winer combined test. The results of the findings among others were that the mean effect size for all the 29 findings examined in effect of indirect instructional method on achievement in chemistry is 0.75 which represents a high effect size. Based on the findings, recommendations were made.